Building evidence around ghost gear: Global trends and analysis for sustainable solutions at scale. (January 2019) - Richardson, Kelsey; Asmutis-Silvia, Regina; Drinkwin, Joan; Gilardi, Kirsten V.K.; Giskes, Ingrid; Jones, Gideon; O'Brien, Kevin; Pragnell-Raasch, Hannah; Ludwig, Laura; Antonelis, Kyle; Barco, Susan; Henry, Allison; et al.
Abstract: Abandoned, lost or discarded fishing gear (ALDFG) comprises a significant amount of global marine debris, with diverse impacts to marine environments, wildlife, and the fishing industry. Building evidence on ALDFG is critical to holistically understand the marine debris issue, and to inform the development of solutions that reduce amounts of ALDFG sources and recover existing gear. Substantial work has been and continues to be undertaken around the world to collect data on ALDFG, much of which remains unpublished. To provide a global picture of data on ALDFG, we organized a technical session that brought together seven ALDFG leaders to share their expertise in data collection, retrieval, and awareness-raising. This paper summarizes the technical session to highlight: 1) case studies that feature innovative approaches to ALDFG data collection and retrieval; 2) examples of opportunities to fill data gaps and improve our understanding of wildlife ingestion of and entanglement in ALDFG; and 3) awareness-raising through the development of a publicly accessible global ALDFG database. Highlights: Abandoned, lost or discarded fishing gear (ALDFG) data is vital to understand impacts and identify solutions Gear loss is ubiquitous, but varies by geography, fisheries and type Citizen scientists and wildlife rehabilitation organizations can fill ALDFG data gaps Entanglement cases should be examined to determine if gear was active or ALDFG The global ALDFG database enables standardization and analysis across disparate data